Parametric study of doubler plate reinforced circular hollow section T-joints at elevated temperature - Foo, Bo Lim (2015)
The Circular Hollow Section (CHS) T-joints can be strengthened by using a ring stiffener both internally and externally or using doubler plates. While such structural behaviors of these reinforced joints under normal temperature have been studied extensively, relatively little work has been done on reinforced joints under elevated temperature. These literature will be further elaborated and explored in the later part of this paper. Nevertheless, this study seeks to provide an insight on this aspect through the use of empirical data, breaching these gaps and the laying the foundation in which further studies can be built on. The aims of this study are achieved and carried out in two phases with the use of the software, ABAQUS to find out whether the theoretical properties of chord to brace ratio would be affected by elevated temperature. Firstly, ABAQUS is employed to run an analysis and simulation of a model resembling a CHS T-joint strengthened with doubler plates as reinforcements for three different sizes brace. After which, another set of simulation would be conducted, using the same software to test the performance of that model under elevated temperature.The results were then compared. A detailed description of process will be presented in the section on “Methodology” later on in the paper.